Composite antibacterial agent packaging film
By using mesoporous nanometal oxides coupled with amine active substances in the cold fresh meat packaging film and grafting the composite antibacterial nanomaterials with plant essential oils, the problem of poor antibacterial effect in the existing cold fresh meat packaging technology is solved, achieving a more lasting antibacterial effect and a lower risk of foodborne diseases.
Patent Information
- Application Number
- CN202411778081.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-15
AI Technical Summary
The existing cold fresh meat packaging technology has problems with poor antibacterial effects, waste of resources and foodborne diseases, especially in complex processing and transportation environments.
A composite antibacterial agent packaging film is designed to react mesoporous nanometal oxides with amine active substances and graft plant essential oils to prepare composite antibacterial nanomaterials with antibacterial functions. The material is prepared by a melt multi-layer coextrusion process, combined with a water-soluble chitosan additive layer, forming microporous channels for diffusion and release of antibacterial components.
It achieves a more lasting antibacterial effect, reduces the volatility of plant essential oils, improves the antibacterial properties of packaging films, extends the shelf life of cold fresh meat and reduces the risk of foodborne diseases.
Smart Images

Figure CN119817598A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging, and in particular to a composite antibacterial agent packaging film. Background Art
[0002] In recent years, due to the quality problems of hot fresh meat and changes in consumer purchasing methods, major supermarkets have gradually begun to sell fresh meat from livestock and poultry, and consumers have gradually become accustomed to buying fresh meat from supermarkets. However, due to the imperfect industrial chain structure and the poor effect of preservation technology, it is often contaminated by bacteria due to improper storage in complex processing and transportation environments, resulting in corruption and deterioration. There are problems such as short shelf life and quality degradation of products. Among them, the growth and reproduction of microorganisms is an important cause of meat corruption. At the same time, the commercially available cold fresh meat mainly adopts relatively simple packaging methods such as plastic wrap and trays, which can only play a simple physical barrier role and have little antibacterial effect. The backward post-slaughter preservation technology seriously restricts the processing and development of cold fresh meat, and also leads to a large amount of resource waste and the occurrence of foodborne diseases. Therefore, the development of an antibacterial packaging with good antibacterial effect, green and safe is the key to the preservation of cold fresh meat.
[0003] Natural active antimicrobial agents such as essential oils and lysozyme come from natural plants and animals and have good biocompatibility, are non-toxic, non-irritating, have high antibacterial activity, and are widely available. Therefore, they have good prospects for use in food packaging antimicrobial materials. However, they also have disadvantages such as poor heat resistance, high volatility, and short antimicrobial efficacy. Therefore, it is very necessary to design and develop an antimicrobial packaging material with added natural active antimicrobial agents through chemical and physical means to meet market demand. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects in the prior art and provide a composite antibacterial agent packaging film and a preparation method thereof to solve the above problems in the prior art.
[0005] To achieve the above object, the technical solution of the present invention is to design a composite antibacterial nanomaterial, which is prepared by coupling reaction of mesoporous nano metal oxide and amine active substances, and then grafting plant essential oil.
[0006] Furthermore, the mesoporous nano-metal oxide is prepared by etching the nano-metal oxide with hydrofluoric acid.
[0007] Furthermore, the nano metal oxide is at least one of nano titanium dioxide, nano zinc oxide, and nano copper oxide.
[0008] Furthermore, the preparation method of the mesoporous nano metal oxide is as follows: The nano-metal oxide is added to a hydrofluoric acid aqueous solution, homogenized, ultrasonicated, and centrifuged to remove the supernatant; then washed with anhydrous ethanol and centrifuged, repeated three times, and vacuum dried to obtain the mesoporous nano-metal oxide; The diameter of the nano metal oxide is 20-500 nm; the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 20-30%; the added concentration of nano metal oxide particles is 20-30 mg / ml; the ultrasonic time is 5-15 min; the centrifugal speed is 8000-15000 r / min, the time is 10-20 min; the vacuum degree is -0.085, and the drying time is 6-24 h.
[0009] Furthermore, the specific steps of coupling reaction between the mesoporous nano-metal oxide and the amine active substance are as follows: The mesoporous nano-metal oxide is dispersed in deionized water, ultrasonically dispersed, an amine active substance is added under magnetic stirring, ammonia water is dropped and an appropriate amount of buffer is added, the pH of the solution is adjusted, the solution is stirred at room temperature for a certain time, the temperature is increased and stirred for a certain time, the supernatant is removed by centrifugation, the reactant is rinsed with anhydrous ethanol for multiple times, centrifuged, and vacuum dried to obtain modified nano-metal oxide particles grafted with the amine active substance; Wherein, the amine active substance is at least one of lysine, histidine, ethylenediamine and dopamine; preferably, the amine active substance is dopamine; the concentration of the mesoporous nano-metal oxide aqueous solution is 10-20 mg / ml; preferably, the concentration of the mesoporous nano-metal oxide aqueous solution is 14-18 mg / ml; most preferably, the concentration of the mesoporous nano-metal oxide aqueous solution is 16 mg / ml; the molar ratio of the amine active substance to the mesoporous nano-metal oxide particles is 1:5-15; preferably, the molar ratio of the amine active substance to the mesoporous nano-metal oxide particles is 1:9-12; most preferably, the molar ratio of the amine active substance to the mesoporous nano-metal oxide particles is 1:10; Add ammonia water and appropriate amount of tris(hydroxymethyl)aminomethane or PBS buffer to adjust the pH to 8-9; Stir at room temperature at a speed of 500-1000r / min for 20-40min; heat to 50-70℃ and continue reaction for 3-5h; centrifuge at a speed of 8000-12000r / min for 10-20min; vacuum degree -0.085, drying time 6-24h.
[0010] Preferably, aqueous ammonia is added dropwise and a tris(hydroxymethyl)aminomethane buffer is added to adjust the pH to 8.5.
[0011] Furthermore, the modified nano-metal oxide particles grafted with the amine active substance and the plant essential oil are dispersed in an anhydrous ethanol solvent, and after ultrasonication, the mixture is stirred and refluxed under nitrogen protection heating conditions, and after sufficient reaction to form a Schiff base structure, the ethanol is removed by rotary evaporation, and the mixture is cooled and allowed to stand for crystallization to obtain composite antibacterial nano-particles grafted with the plant essential oil and having antibacterial function; Among them, the plant essential oil is one or two of cinnamaldehyde and perilla aldehyde; the weight ratio of the plant essential oil to the modified nano-metal oxide particles grafted with polydopamine is 1:2~3, and the solution concentration is 50-100mg / ml; ultrasonic dispersion is 5-20min, heating temperature is 70-90℃, stirring speed is 600-1000r / min, reflux is 4-8h; cooling and standing is 4-8h.
[0012] A composite antibacterial nano material can be used for packaging films, bags, sheets and fiber materials.
[0013] A composite antimicrobial packaging film includes a first functional layer to which a composite antimicrobial nanomaterial is added, and the weight proportion of the composite antimicrobial nanomaterial in the first functional layer is 3-10%. Specifically, the weight proportion of the composite antimicrobial nanomaterial in the first functional layer can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, and any range between the aforementioned values.
[0014] Preferably, the first functional layer comprises 15-100 parts by weight of composite antibacterial nanomaterial masterbatch and 0-85 parts by weight of substrate; the substrate is one or more of LDPE, LLDPE, EVA, and POE.
[0015] Preferably, the first functional layer comprises 15-100 parts by weight of composite antibacterial nanomaterial masterbatch and 0-85 parts by weight of LLDPE.
[0016] Most preferably, the first functional layer comprises 50 parts of composite antibacterial nanomaterial masterbatch and 50 parts of LLDPE by weight.
[0017] Wherein, the composite antibacterial nanomaterial masterbatch is prepared as follows: The composite antibacterial nano material particles are mixed with resin in a weight ratio of 1:3-9, and a twin-screw extruder is used for mixing, extruding and granulating to obtain a composite antibacterial nano material masterbatch; the resin is one of PE, PP, PA and PET.
[0018] Preferably, the composite antibacterial nanomaterial masterbatch is prepared as follows: The composite antibacterial nano material particles and the resin are mixed in a weight ratio of 1:4, and a twin-screw extruder is used for mixing, extruding and granulating to obtain a composite antibacterial nano material masterbatch; the resin is PE.
[0019] Furthermore, it also includes a substrate layer, which is composed of at least one of polyethylene (PE), polyamide (PA), polyvinylidene chloride (PVDC), ethylene-vinyl alcohol copolymer (EVOH), ethylene-vinyl acetate copolymer (EVA), anhydride-modified polyethylene (TIE), polyester (PET), polyolefin elastomer (POE), etc., and the first functional layer is arranged on the substrate layer.
[0020] Furthermore, it also includes a second functional layer, which is arranged on the side of the first functional layer away from the substrate layer; the second functional layer includes 15-90 parts by weight of water-soluble chitosan masterbatch and 10-85 parts of substrate; the substrate is one or more of LDPE, LLDPE, MLLDPE, EVA, and POE; Preferably, the second functional layer comprises 15-90 parts by weight of water-soluble chitosan masterbatch, 10-85 parts of LLDPE, and 0-75 parts of MLLDPE; Preferably, the second functional layer comprises 25 parts of water-soluble chitosan masterbatch, 45 parts of LLDPE and 30 parts of MLLDPE by weight.
[0021] Preferably, the second functional layer comprises 75 parts of water-soluble chitosan masterbatch, 10 parts of LLDPE and 15 parts of MLLDPE by weight.
[0022] Wherein, the water-soluble chitosan masterbatch is prepared as follows: The water-soluble chitosan and the resin are mixed in a weight ratio of 1:2-5, and a twin-screw extruder is used for mixing, extruding and granulating to obtain a composite antibacterial nanomaterial masterbatch; the resin is one of PE, PP, PA and PET.
[0023] Preferably, the water-soluble chitosan masterbatch is prepared as follows: The water-soluble chitosan and the resin are mixed in a weight ratio of 1:4, and a twin-screw extruder is used for mixing, extruding and granulating to obtain a composite antibacterial nanomaterial masterbatch; the resin is PE.
[0024] Preferably, the water-soluble chitosan is one or both of small molecule chitosan and carboxymethyl chitosan.
[0025] Preferably, the weight proportion of the water-soluble chitosan in the second functional layer is 5-15%. Specifically, the weight proportion of the water-soluble chitosan in the second functional layer can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15% and ranges between any of the aforementioned values.
[0026] The composite antibacterial agent packaging film is prepared by a melt multi-layer co-extrusion process and has a thickness of 20-300 μm, wherein the first functional layer accounts for 10-20% of the total thickness of the film, and the second functional layer accounts for 5-20% of the total thickness of the film.
[0027] The advantages and beneficial effects of the present invention are as follows: the water-soluble chitosan added layer of the present invention covers the composite antibacterial nanoparticle added layer during the high-temperature melt extrusion process, thereby preventing the effective antibacterial component essential oil therein from volatilizing; during use, the water-soluble chitosan dissolves after encountering water, forming a series of microporous channels in the film layer, connecting the external environment with the composite antibacterial nanoparticle added layer, and facilitating the diffusion and migration of the antibacterial effective components to the surface of the film material. In addition, by etching the nano-metal oxide particles to form a mesoporous structure, the specific surface area of the nano-particles is increased, and the amount of amine active substances grafted on the surface of the nano-metal oxide particles is increased, which provides conditions for the subsequent grafting of more natural active antibacterial plant essential oils, making the antibacterial effect more durable, and the grafting of plant essential oils with polydopamine increases the stability of the essential oils during the high-temperature extrusion process and reduces volatilization. The Schiff base structure generated by the grafting of plant essential oils and polydopamine is easily hydrolyzed. During the packaging process, moisture diffuses through the microporous channels of the water-soluble chitosan added layer to the composite antibacterial nanoparticle added layer. The hydrolysis of the Schiff base structure releases the essential oil and diffuses it to the surface of the membrane material, achieving a controlled release and antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the structural diagram of the composite antimicrobial agent packaging film; Figure 2 The structural diagram of the packaging film prepared in Examples 1, 2, and 3; Figure 3 This is a structural diagram of the packaging film prepared in Comparative Example 1; Figure 4 This is a structural diagram of the packaging film prepared in Comparative Example 2. DETAILED DESCRIPTION
[0029] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0030] The manufacturers and models of the raw materials in the embodiments and comparative examples are as follows: Rutile nano-titanium dioxide: T818935, Shanghai MacLean Biochemical Technology Co., Ltd. Dopamine: A902400, Shanghai MacLean Biochemical Technology Co., Ltd. Essential oil: Cinnamaldehyde S24035, Shanghai Yuanye Biological Co., Ltd. Carboxymethyl chitosan: S30948, Shanghai Yuanye Biotechnology Co., Ltd. Polyamide (PA): ULTRAMID, BASF China Polyethylene (PE): DOWLEX, Dow Chemical Anhydride modified polyethylene (TIE): MODIC, Mitsubishi Chemical 1. Implementation Example 1 The preparation method of the composite antimicrobial agent packaging film is as follows: Step S1: preparing functional additive composite antibacterial nanomaterials, the specific preparation steps are as follows: (1) Add 2 g of rutile nano-titanium dioxide with a particle size of 25 nm to 100 ml of a 30% hydrofluoric acid aqueous solution, shake with a homogenizer, ultrasonicate for 10 min, and centrifuge at 10,000 r / min for 15 min; remove the supernatant, dissolve with anhydrous ethanol, wash the centrifugal precipitate with ultrasonication for 5 min, and then centrifuge at 10,000 r / min for 15 min. Repeat this process three times; place the resulting reactant in a vacuum drying oven with a vacuum degree of -0.085 and a drying time of 12 h to obtain mesoporous nano-titanium dioxide particles; (2) Dissolve 1.6 g of mesoporous nano-titanium dioxide particles in 100 ml of deionized water, and ultrasonicate for 5 min to make them uniformly dispersed. During magnetic stirring, add 0.3 g of dopamine (DA), drop ammonia water and add tris(hydroxymethyl)aminomethane buffer solution, and adjust the pH to 8.5; stir at 800 r / min for 30 min at room temperature; heat to 60°C and continue to react for 4 h; centrifuge at 10,000 r / min for 15 min, remove the supernatant and obtain the reactant; dissolve the reactant in anhydrous ethanol, wash the centrifugal precipitate by ultrasonication for 5 min, and then centrifuge at 10,000 r / min for 15 min. Repeat this process three times; place the obtained reactant in a vacuum drying oven with a vacuum degree of -0.085 and a drying time of 12 h to obtain modified nano-metal oxide particles grafted with polydopamine; (3) 3.4 g of modified nano-metal oxide particles grafted with polydopamine and 1.6 g of cinnamaldehyde essential oil were dispersed in 100 ml of anhydrous ethanol solvent, and after ultrasonication for 10 min, the mixture was stirred at 800 r / min under nitrogen protection at 80 °C, and refluxed for 6 h. After sufficient reaction, the ethanol was removed by rotary evaporation, and the mixture was cooled and allowed to stand for 6 h for crystallization to obtain a composite antibacterial nanomaterial grafted with plant essential oil and having antibacterial function; Step S2: preparing composite antibacterial nanoparticle masterbatch, the specific preparation steps are as follows: The functional additive composite antibacterial nanoparticles and polyethylene resin are mixed in a weight ratio of 1:4, and mixed and extruded at 200° C. using a twin-screw extruder to obtain a composite antibacterial nanoparticle masterbatch in which the weight of the functional additive accounts for 20%; Step S3: preparing water-soluble chitosan masterbatch, the specific preparation steps are as follows: Carboxymethyl chitosan and polyethylene resin are mixed in a weight ratio of 1:4, and mixed and extruded into granules at 200° C. using a twin-screw extruder to obtain a carboxymethyl chitosan masterbatch containing 20% by weight of functional additives; Step S4: adopting a melt 8-layer co-extrusion process, through the processes of melting, extrusion, blow molding, cooling, slitting, and winding, a film with a total thickness of 95 μm is obtained, and the material design of each layer is from outside to inside PA / TIE / PE / TIE / PA / TIE / first functional layer / second functional layer; Among them, in step S4, 25 parts by weight of carboxymethyl chitosan masterbatch, 45 parts by weight of LLDPE and 30 parts by weight of MLLDPE are added to the second functional layer to form a functional layer with a carboxymethyl chitosan addition amount of 5% and a layer thickness of 10 μm; 50 parts by weight of composite antibacterial nanoparticle masterbatch and 50 parts by weight of LLDPE are added to the first functional layer to form a functional layer with a composite antibacterial nanoparticle addition amount of 10% and a layer thickness of 15 μm, and the overall layer thickness is 20 / 5 / 20 / 5 / 15 / 5 / 15 / 10 from the outside to the inside, and a composite antibacterial agent packaging film is obtained.
[0031] Embodiment 2: Compared with Example 1, the only difference is that step S4 is different, which is as follows: The 8-layer co-extrusion process was adopted, and a film with a total thickness of 95 μm was obtained through the processes of melting, extrusion, blow molding, cooling, slitting, and winding. The material design of each layer was from outside to inside PA / TIE / PE / TIE / PA / TIE / first functional layer / second functional layer. In the second functional layer, 75 parts by weight of carboxymethyl chitosan masterbatch, 10 parts by weight of LLDPE, and 15 parts by weight of MLLDPE were added to form a functional layer with a carboxymethyl chitosan addition ratio of 15% and a layer thickness of 10 μm; in the first functional layer, 50 parts by weight of composite antibacterial nanoparticle masterbatch and 50 parts by weight of LLDPE were added to form a functional layer with a composite antibacterial nanoparticle addition ratio of 10% and a layer thickness of 15 μm. The overall layer thickness was 20 / 5 / 20 / 5 / 15 / 5 / 15 / 10 from outside to inside, and a composite antibacterial agent packaging film was obtained.
[0032] Embodiment 3: Compared with Example 1, the only difference is that step S4 is different, which is as follows: The 8-layer co-extrusion process was adopted, and a film with a total thickness of 95 μm was obtained through the processes of melting, extrusion, blow molding, cooling, slitting, and winding. The material design of each layer was from outside to inside PA / TIE / PE / TIE / PA / TIE / first functional layer / second functional layer. In the second functional layer, 25 parts by weight of carboxymethyl chitosan masterbatch, 45 parts by weight of LLDPE, and 30 parts by weight of MLLDPE were added to form a functional layer with a carboxymethyl chitosan addition ratio of 5% and a layer thickness of 10 μm; in the first functional layer, 15 parts by weight of composite antibacterial nanoparticle masterbatch and 85 parts by weight of LLDPE were added to form a functional layer with a composite antibacterial nanoparticle addition ratio of 3% and a layer thickness of 15 μm. The overall layer thickness was 20 / 5 / 20 / 5 / 15 / 5 / 15 / 10 from outside to inside, and a composite antibacterial agent packaging film was obtained.
[0033] Comparative Example 1: Compared with Example 1, the only difference is that only steps S3 and S4 are different, as follows: In Comparative Example 1, step S3 is not included, and carboxymethyl chitosan masterbatch is not added to the second functional layer; Step S4 is as follows: adopt a melt 8-layer co-extrusion process, through melting, extrusion, blow molding, cooling, slitting, and winding processes, to obtain a film with a total thickness of 95 μm, and the material design of each layer is from outside to inside PA / TIE / PE / TIE / PA / TIE / first functional layer / PE. Add 50 parts by weight of composite antibacterial nanoparticle masterbatch and 50 parts by weight of LLDPE to form a functional layer with a composite antibacterial nanoparticle addition accounting for 10%, a layer thickness of 15 μm, and an overall layer thickness of 20 / 5 / 20 / 5 / 15 / 5 / 15 / 10 from outside to inside, to obtain a composite antibacterial agent packaging film.
[0034] Comparative Example 2: Compared with Example 1, the only difference is that only steps S3 and S4 are different, as follows: In comparative example 2, there is no step S3, and in step S4, no second functional layer is provided, so that the first functional layer is directly exposed to the inner surface layer and directly contacts the external environment, and the number of substrate layers is adaptively adjusted to ensure that the total number of layers of the composite antimicrobial agent packaging film is still 8 layers.
[0035] Step S4 is specifically as follows: The 8-layer co-extrusion process was adopted, and a film with a total thickness of 95 μm was obtained through the processes of melting, extrusion, blow molding, cooling, slitting, and winding. The material design of each layer was from outside to inside PA / TIE / PE / TIE / PA / TIE / PE / first functional layer. In the first functional layer, 50 parts by weight of composite antibacterial nanoparticle masterbatch and 50 parts by weight of LLDPE were added to form a functional layer with a composite antibacterial nanoparticle addition ratio of 10%, a layer thickness of 15 μm, and an overall layer thickness of 20 / 5 / 20 / 5 / 15 / 5 / 10 / 15 from outside to inside, to obtain a composite antibacterial agent packaging film.
[0036] (II) Performance test (1) Test method The antibacterial experiment was carried out with reference to the experimental method of ISO 22196-2011 "Evaluation of Antimicrobial Properties of Plastic Products Surfaces". The spoilage of fresh meat is caused by the presence of spoilage bacteria. Therefore, Pseudomonas was selected as the test bacteria in the antibacterial experiment. The antibacterial properties of the material were evaluated through the processes of bacterial liquid activation, dilution, film culture, flushing and dilution, plate culture, and plate counting.
[0037] (2) Experimental test results Antibacterial rate 6h 12h 18h 24h 2D 3D Example 1 58.35 73.23 89.71 98.1 99.99 99.99 Example 2 71.56 85.78 96.23 99.99 99.99 99.99 Example 3 53.5 61.2 75.28 85.04 93.72 99.99 Comparative Example 1 0 0 0 0 0 0 Comparative Example 2 65.4 74.98 81.75 86.77 88.09 88.12 Comparison between Example 1 and Comparative Example 1 shows that the composite antibacterial nanoparticles are added to the second layer, and the first layer is covered with conventional polyethylene materials, which will affect the diffusion of the effective ingredients and have no antibacterial effect; while the carboxymethyl chitosan added layer is used for covering, the chitosan exhibits antibacterial properties in the initial stage, and forms microporous channels after absorbing water and dissolving. Water diffuses to the second layer through the channels, causing the Schiff base structure between the plant essential oil and polydopamine to hydrolyze, and the essential oil components are released and diffused to the bacterial contact surface through the channels, and the antibacterial rate rises rapidly. At the same time, it shows that the design of the water-soluble chitosan added layer can effectively release the antibacterial substances in the second layer.
[0038] Comparison between Example 1 and Comparative Example 2 shows that the antibacterial rate of Example 1 is not as good as that of Comparative Example 2 in the early stage, because it takes time for the essential oil components to diffuse and precipitate, and the antibacterial rate in the early stage mainly depends on the first functional layer of carboxymethyl chitosan. As time goes by, the antibacterial rate of Example 1 increases rapidly, because carboxymethyl chitosan dissolves in the first layer to form microporous channels, and the effective components of the second layer of essential oils are hydrolyzed and migrated out faster. The overall antibacterial effect of the final material in Example 1 is better than that in Comparative Example 2, because the high-temperature extrusion process of adding essential oils to the surface layer causes hydrolysis and volatilization, resulting in loss of effective components, and the overall antibacterial rate is not as good as that of Example 1 with covering protection. It can be concluded that the structural optimization design of adding effective antibacterial substances to the first functional layer and covering with the second functional layer can effectively reduce the volatilization loss of essential oils under high temperature conditions.
[0039] Comparison of Examples 1, 2, and 3 shows that with the increase in the amount of water-soluble chitosan and composite antibacterial nanoparticles added, the antibacterial efficiency of the membrane material is rapidly improved, which is due to the increase in the amount of microporous channels formed and the increase in antibacterial effective ingredients.
[0040] The properties of the composite antibacterial nanoparticles combined with the water-soluble chitosan added layer can solve the problem of essential oil volatilization and ensure the excellent antibacterial properties of the packaging film.
[0041] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composite antibacterial nanomaterial, characterized in that: The nanostructured polymer is prepared by coupling a mesoporous nano-metal oxide with an amine active substance and then grafting plant essential oil.
2. A composite antibacterial nanomaterial according to claim 1, characterized in that: The mesoporous nano metal oxide is prepared by etching the nano metal oxide with hydrofluoric acid.
3. A composite antibacterial nanomaterial according to claim 2, characterized in that: The preparation method of the mesoporous nano metal oxide is as follows: The nano-metal oxide is added to a hydrofluoric acid aqueous solution, homogenized, ultrasonicated, and centrifuged to remove the supernatant; then washed with anhydrous ethanol and centrifuged, repeated for multiple times, and then vacuum dried to obtain the mesoporous nano-metal oxide; The diameter of the nano metal oxide is 20-500 nm; the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 20-30%; the concentration of nano metal oxide particles added is 20-30 mg / ml; the ultrasonic time is 5-15 min; the centrifugal speed is 8000-15000 r / min, the time is 10-20 min; and the vacuum drying time is 6-24 h.
4. The composite antibacterial nanomaterial according to claim 1, characterized in that: The specific steps of the coupling reaction between the mesoporous nano metal oxide and the amine active substance are as follows: The mesoporous nano-metal oxide is dispersed in deionized water, ultrasonically dispersed, an amine active substance is added under magnetic stirring, ammonia water is dropped and an appropriate amount of buffer is added, the pH of the solution is adjusted, the solution is stirred at room temperature for a certain time, the temperature is increased and stirred for a certain time, the supernatant is removed by centrifugation, the reactant is rinsed with anhydrous ethanol for multiple times, centrifuged, and vacuum dried to obtain modified nano-metal oxide particles grafted with the amine active substance; The amine active substance is at least one of lysine, histidine, ethylenediamine and dopamine; the concentration of the mesoporous nano-metal oxide aqueous solution is 10-20 mg / ml, and the molar ratio of the amine active substance to the mesoporous nano-metal oxide particles is 1:5-15; Add ammonia water and appropriate amount of tris(hydroxymethyl)aminomethane or PBS buffer to adjust the pH to 8-9; Stir at room temperature at a speed of 500-1000r / min for 20-40min; heat to 50-70℃ and continue reaction for 3-5h; centrifuge at a speed of 8000-12000r / min for 10-20min; vacuum degree -0.085, drying time 6-24h.
5. The composite antibacterial nanomaterial according to claim 4, characterized in that: The modified nano-metal oxide particles grafted with amine active substances and plant essential oils are dispersed in anhydrous ethanol solvent, and after ultrasonication, the mixture is stirred and refluxed under nitrogen protection heating conditions, and after sufficient reaction to form a Schiff base structure, the ethanol is removed by rotary evaporation, and the mixture is cooled and allowed to stand for crystallization to obtain composite antibacterial nano-particles grafted with plant essential oils and having antibacterial function; Among them, the plant essential oil is one or two of cinnamaldehyde and perilla aldehyde; the weight ratio of the plant essential oil to the modified nano-metal oxide particles grafted with amine active substances is 1:2~3, and the solution concentration is 50-100mg / ml; ultrasonic dispersion is 5-20min, heating temperature is 70-90℃, stirring speed is 600-1000r / min, reflux is 4-8h; cooling and standing is 4-8h.
6. The composite antibacterial nanomaterial according to claim 2, characterized in that: The nano metal oxide is at least one of nano titanium dioxide, nano zinc oxide and nano copper oxide.
7. A composite antibacterial nanomaterial as claimed in any one of claims 1 to 6, which can be used in the preparation of packaging films, bags, sheets and fiber materials.
8. A composite antimicrobial agent packaging film, characterized in that: It comprises a first functional layer to which the composite antibacterial nanomaterial according to any one of claims 1 to 6 is added, and the weight proportion of the composite antibacterial nanomaterial in the first functional layer is 3-10%.
9. The composite antimicrobial agent packaging film according to claim 8, characterized in that: It also includes a substrate layer, which is composed of at least one of polyethylene (PE), polyamide (PA), polyvinylidene chloride (PVDC), ethylene-vinyl alcohol copolymer (EVOH), ethylene-vinyl acetate copolymer (EVA), anhydride-modified polyethylene (TIE), polyester (PET), and polyolefin elastomer (POE), and the first functional layer is arranged on the substrate layer.
10. The composite antimicrobial agent packaging film according to claim 9, characterized in that: It also includes a second functional layer, which is arranged on the side of the first functional layer away from the substrate layer; the second functional layer is added with water-soluble chitosan; the water-soluble chitosan is one or both of small molecule chitosan and carboxymethyl chitosan, and the water-soluble chitosan accounts for 5-15% of the weight of the second functional layer.